2015
DOI: 10.3109/03009742.2015.1006247
|View full text |Cite
|
Sign up to set email alerts
|

Platelet counts as a biomarker in ANCA-associated vasculitis

Abstract: PLT counts were found to correlate with disease activity in AAV and thus may be used to represent immunological activity. In addition, PLT counts serve as a marker that can distinguish acute infection from active disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 26 publications
1
27
4
1
Order By: Relevance
“…On the contrary, research on platelet (PLT) counts, which are an acknowledged inflammatory marker, found elevated PLT counts in patients with active disease, compared to patients in remission, and also elevated PLT counts in AAV patients with active disease, compared to AAV patients with infection, thus highlighting their role as an AAV specific marker of disease activity [15].…”
Section: Biomarkers In Aavmentioning
confidence: 99%
“…On the contrary, research on platelet (PLT) counts, which are an acknowledged inflammatory marker, found elevated PLT counts in patients with active disease, compared to patients in remission, and also elevated PLT counts in AAV patients with active disease, compared to AAV patients with infection, thus highlighting their role as an AAV specific marker of disease activity [15].…”
Section: Biomarkers In Aavmentioning
confidence: 99%
“…В свою очередь, активированные тромбоциты могут инициировать запуск системы комплемента путем повышения синтеза С3а, С3b и формирования C5аb-9 [46]. В пользу этой гипотезы свидетельствует и высокая частота развития тромбоцитоза у пациентов с активными формами ААВ, а также взаимосвязь числа тромбоцитов с показателями активности заболевания [47].…”
Section: взаимосвязь тромбоэмболических осложнений и системы комплемеunclassified
“…Increasing studies demonstrate a high prevalence of venous thromboembolic event (VTE) and a hypercoagulant state in AAV patients [ 6 11 ]. In the active stage of AAV, the platelet count is usually elevated [ 10 , 12 ]. In addition to their classic hemostatic role, platelets are also inflammation protagonists [ 13 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Platelets and the soluble molecules that they secrete can mediate inflammatory responses and thus contribute to vascular injury [ 17 , 18 ]. An association between some platelet indices, including platelet counts, mean platelet volume, and disease activity have been reported in AAV and several other autoimmune diseases, such as inflammatory bowel disease, ankylosing spondylitis and rheumatoid arthritis [ 10 , 12 , 19 21 ].…”
Section: Introductionmentioning
confidence: 99%